HUBUNGAN PERILAKU PETUGAS KESEHATAN TERHADAP KELENGKAPAN ISI DOKUMEN REKAM MEDIS DI RUMAH SAKIT KOTA MALANG (Studi Kasus di RSIA Puri Malang) - Basuki, Rinawati; Dewi, Endang Sri; Sundari, Siti (DINAMIKA DOTCOM, 2017)
The purpose of this research is to find out the correlation between health officer behavior toward the completeness of document medical record content in Malang city hospital. The type of this research is correlational analytic research with Cross sectional approach, to obtain knowledgedata, attitude of hospital officer related to filling medical record and completeness of medical record document of hospital patient. Methods of research number of respondents 32 research period August 2014 results of research a) There are 76.3% of respondents with good knowledge and 23.7% of respondents with sufficient knowledge criteria, no one knowledgeable less. The highest level of consecutive knowledge is doctor, registrant, midwife and nurse, b) There are 42.1% of respondents who have attitude about medical record with positive category and 57.9% of respondents who have attitude with negative category. The highest value of consecutive attitudinal attitudes are doctors, registrants, midwives and nurses,C) Completeness of medical record document is 79.9%.Keywords: simple random sampling, Cross sectional approach, hospital officer attitude related to medical record, Informed Concent, Anomity, Confidentiality